Behçet’s syndrome in pediatric age - Mendes, Ana Raquel (2020)
Introduction: Behçet's syndrome is a systemic vasculitis characterized by recurrent oral and/or genital ulcers, and several systemic manifestations. The authors describe the case of a pediatric-onset Behçet's syndrome. Case report: An 11-year-old boy was referred to the Pediatric consultation after two episodes of great saphenous vein thrombophlebitis. He had experienced daily oral aphthae for the past three years, and various episodes of folliculitis with pustule formation. Laboratory study was normal. The boy showed no signs of uveitis. The diagnosis of Behçet's syndrome diagnosis was established according to the international criteria, with positive HLA- B51 testing. Colchicine was initiated, with favourable response. Conclusions: Due to clinical feature overlap with other conditions, Behçet's syndrome diagnosis remains challenging. Consensus pediatric classification criteria developed in 2016 enabled greater sensitivity and earlier diagnosis.